PENGARUH ASAL SEKOLAH DAN TEMPAT TINGGAL TERHADAP PRESTASI BELAJAR MAHASISWA - Ratna Indriyani (Wiraraja Medika : Jurnal Kesehatan, 2014)
Background of Study : Main problem faces education world nowadays is the low level on University Student’s achievement. and to reach certain expected achievement, it is needed to pay attention on some influence factors. As Anni stated o 2004 that there are 2 factors which influence on educational achievement, i.e internal and external factors. While purpose of this research is to know the influence of student’s origin school and home Toward education achievement on University Student In D-III Faculty Of Midwifery Wiraraja University year 2014. Research Methodology : Research design use in this research is Cross sectional as correlational analytic. While respondents population are 52 taken from third semester students in D-III Faculty Of Midwifery Wiraraja University year 2013 – 2014.  And instrument use to collect data is in form of documentation and interview. Further, the bivariate data is analyzed by using chi-square test and the multivariate data is analyzed by using ordinal logistic regression test. Result of the Research : Based on the bivariate analysis it is known that there is a correlation between origin schools toward educational achievement with the significant score on 0,009 < 0,005.  Also there is a correlation between homes toward educational achievement with the significant score on 0,011 < 0,05. While the multivariate analysis shows that there is correlation between origin schools toward educational achievement with significant score on 0,008 < 0,05. Also there is a correlation between homes toward educational achievement with the significant score on 0,40< 0,05.Conclusion : From the research it is concluded that there is influence between student’s origin schools and homes toward education achievement on university student in D-III Faculty Of Midwifery Wiraraja University. Keyword        : origin schools, homes, educational achievement